METODE SKOR KONSUMSI PANGAN UNTUK MENILAI KETAHANAN PANGAN RUMAH TANGGA - Anita Christina Sembiring; Dodik Briawan; Yayuk Farida Baliwati (Persagi, 2015)
ABSTRACTThis study is aimed to test food consumption score (FCS) methods to assess the food insecurity in households at risk in the city of Bogor. The design of research is cross-sectional with number of respondents as much as 98 households. Food consumption score (FCS) describes the sum of all scores of eight food groups by multiplying the weight and frequency of each food group. The level of nutritional adequacy is measured by nutrientadequacy ratio (NAR) and the mean adequacy ratio (MAR). Sensitivity and specificity analysis are performed to determine the cut off point most appropriate from FCS to identify households at risk of food insecurity(sensitivity) and household food security (specificity). Spearman correlation test results showed that there are significant relationship between FCS and MAR (r = 0,548) and between FCS and percent RDA of energy (r =0,282). Cut off point 89 for minimal score is able to identify food-insecure households (MAR <77 percent) with 82 percent sensitivity and 82 percent specificity, and to identify TKE <70 percent with 70 percent sensitivity and67 percent specificity. FCS can be used to identify food insecurity in household at risk by using a cut-off point that has been modified.Keywords: food consumption score, food security, householdABSTRAKPenelitian ini bertujuan menguji coba metode food consumption score (FCS) untuk menilai ketahanan pangan pada rumah tangga yang berisiko rawan pangan di Kota Bogor. Desain penelitian potong lintang denganjumlah responden sebanyak 98 rumah tangga. Food consumption score (FCS) menjelaskan jumlah semua skor dari delapan kelompok pangan dengan cara mengalikan bobot dan frekuensi dari masing-masing kelompok pangan. Tingkat kecukupan gizi diukur dengan nutrient adequacy ratio (NAR) dan mean adequacy ratio (MAR). Analisis sensitivitas dan spesifisitas dilakukan untuk menentukan cut-off point yang paling tepat dari FCS untuk mengidentifikasi rumah tangga yang berisiko rawan pangan (sensitivitas) dan rumah tangga yang tahan pangan (spesifisitas). Hasil uji korelasi Spearman menunjukkan bahwa ada hubungan yang signifikan antara FCS dan MAR (r=0,548) dan ada hubungan yang signifikan antara FCS dan tingkat kecukupan energi (TKE)(r=0,282). Cut-off 89 untuk skor minimal FCS mampu mengidentifikasi rumah tangga yang rawan pangan (MAR<77%) dengan sensitifitas 82 persen dan spesifisitas 82 persen dan mampu mengidentifikasi TKE kurang dari 70 persen dengan sensitivitas 70 persen dan spesifisitas 67 persen. FCS dapat digunakan untuk mengidentifikasi ketahanan pangan pada rumah tangga yang berisiko rawan pangan dengan menggunakancut-off yang telah dimodifikasi. [Penel Gizi Makan 2015, 38(1): 31-40]Kata kunci: food consumption score, ketahanan pangan, rumah tangga